Assessing Dysferlinopathy Patients Over Three Years With a New Motor Scale. Issue 5 (26th February 2021) - Jacobs, Marni B.; James, Meredith K.; Lowes, Linda P.; Alfano, Lindsay N.; Eagle, Michelle; Muni Lofra, Robert; Moore, Ursula; Feng, Jia; Rufibach, Laura E.; Rose, Kristy; Duong, Tina; Bello, Luca; et al.
Abstract : Objective: Dysferlinopathy is a muscular dystrophy with a highly variable clinical presentation and currently unpredictable progression. This variability and unpredictability presents difficulties for prognostication and clinical trial design. The Jain Clinical Outcomes Study of Dysferlinopathy aims to establish the validity of the North Star Assessment for Limb Girdle Type Muscular Dystrophies (NSAD) scale and identify factors that influence the rate of disease progression using NSAD. Methods: We collected a longitudinal series of functional assessments from 187 patients with dysferlinopathy over 3 years. Rasch analysis was used to develop the NSAD, a motor performance scale suitable for ambulant and nonambulant patients. Generalized estimating equations were used to evaluate the impact of patient factors on outcome trajectories. Results: The NSAD detected significant change in clinical progression over 1 year. The steepest functional decline occurred during the first 10 years after symptom onset, with more rapid decline noted in patients who developed symptoms at a younger age ( p = 0.04). The most rapidly deteriorating group over the study was patients 3 to 8 years post symptom onset at baseline. Interpretation: The NSAD is the first validated limb girdle specific scale of motor performance, suitable for use in clinical practice and clinical trials. Longitudinal analysis showed it may be possible to identify patient factors associated with greater functional decline both across the disease course and in the short‐term for clinical trial preparation. Through further work and validation in this cohort, we anticipate that a disease model incorporating functional performance will allow for more accurate prognosis for patients with dysferlinopathy. ANN NEUROL 2021;89:967–978